Intraday futures market behaviour around major scheduled macroeconomic announcements: Australian evidence - Frino, Alex; Hill, Amelia (Journal of Banking & Finance, 2001)
This paper examines intraday futures market behaviour around major scheduled macroeconomic information announcements on the Sydney Futures Exchange (SFE). Prior literature analysing intraday price behaviour around announcements is extended to trading volume and quoted bid–ask spreads. The analysis of price volatility, trading volume and quoted bid–ask spreads indicates that the majority of adjustment to new information occurs rapidly, within 240 seconds of the scheduled time for major announcements, with some evidence of abnormal activity prior to announcements. Analysis of quoted bid–ask spreads suggests that they significantly widen in the 20 seconds prior to announcements and remain significantly wider for 30 seconds following announcements. The increase in quoted spreads is related to both expected and unexpected volatility, implying that market participants increase quoted spreads around information announcements as a consequence of adverse selection costs.